Breaking down embolic strokes of undetermined source for extra cardiac shunts - Azhar, Naveen; Navaira Shoaib; Maria Shoaib (Journal of the Pakistan Medical Association, 2026)
Acute ischaemic stroke remains the leading cause of mortality and disability worldwide warranting medical providers to its aetiologies to guide appropriate secondary prevention. The diagnostic challenge revolves around 30 to 40% cases that remains cryptogenic despite comprehensive evaluation.1 The article aim to highlight some of the cryptogenic aetiologies’, particularly extracardiac shunts, for which clinicians should consider additional investigation. The less commonly considered aetiology, which can similarly allow venous thromboembolic to bypass pulmonary filtration and enter the systemic circulation, is the extracardiac right to left shunts (ECRLS).2 These are abnormal vascular connections, including Pulmonary arteriovenous malformations (PAVMs), pulmonary Fistulas and Porto pulmonary anastomoses.3 Extracardiac shunts are rare but important considerations in patients with embolic strokes of undetermined source (ESUS), particularly in the absence of atrial fibrillation or significant atherosclerosis. Due to their variable presentation and lack of standardised screening protocols, the clinical detection of ECRLS is often challenging. Contrast-enhanced transcranial Doppler (cTCD) and transthoracic or transoesophageal echocardiography, especially when performed with agitated saline and manoeuvres such as the Valsalva, are critical for diagnosis. A delayed appearance of microbubbles in the left heart or cerebral circulation can help unmask these shunts when initial investigations are inconclusive.4 Furthermore, the pathophysiology of ECRLS is distinct from that of intracardiac shunts, a nuance demands further researchers’ attention.5 A discussion of the current evidence on extracardiac shunts may help identify treatable causes cryptogenic stroke. Though increased awareness and methodical evaluation, clinicians can broaden the differential diagnosis of cryptogenic stroke and improve patient outcomes by addressing this underappreciated aetiologies.